Teaching within a Story: Understanding storification of pedagogy. (2021) - Aura, Isabella; Hassan, Lobna; Hamari, Juho
Highlights: Storification can be employed in teaching practices to make education more engaging. Storified pedagogy empowered students and created a comfortable school atmosphere. Storified learning environment decreased student misconduct. Storification can enhance the academic performance of students at-risk. Abstract: Storification is an emerging pedagogical technique, albeit research lacks the understanding of its benefits and detriments. This study examines a school in the US that has storified majority of their learning environment into various fictional and nonfictional worlds for students to learn in and for teachers to incorporate in their pedagogy. 11 educational staff and 79 students were interviewed, and classes were observed for 10 days to ground a theory of storified pedagogy. Storification, employed in physical learning environments and in teaching practices, supported pedagogy and decreased student misconduct at the school. Storified pedagogy empowered students through story morals and a sense of transportation, and enabled classrooms to turn into personalized spaces, enhancing the school experience and students' academic performance.